Aggregatibacter actinomycetemcomitans Leukotoxin Activates the NLRP3 Inflammasome and Cell-to-Cell Communication - Peyman Kelk; Nick Sina Moghbel; Josefine Hirschfeld; Anders Johansson (Pathogens, 2022)
Carriers of highly leukotoxic genotypes of Aggregatibacter actinomycetemcomitans are at high risk for rapid degradation of tooth-supporting tissues. The leukotoxin (LtxA) expressed by this bacterium induces a rapid pro-inflammatory response in leukocytes that results in cell death. The aim of the present study was to increase the understanding of LtxA-induced leukocyte activation mechanisms and of possible associated osteoclast differentiation. The effect of LtxA on activation of the inflammasome complex was studied in THP-1 wild type and in NLRP3- and ASC knockout cells. Cell-to-cell communication was assessed by fluorescent parachute assays, and THP-1 differentiation into osteoclast-like cells was investigated microscopically. The results showed that LtxA induced inflammatory cell death, which involved activation of the NLRP3 inflammasome and gap junction cell-to-cell communication. THP-1 cells treated with lipopolysaccharide (LPS) and LtxA together differentiated into an osteoclast-like phenotype. Here, LPS prevented LtxA-mediated cell death but failed to induce osteoclast differentiation on its own. However, pit formation was not significantly enhanced by LtxA. We conclude that A. actinomycetemcomitans leukotoxicity mediates activation of the NLRP3 inflammasome and cell-to-cell communication in the induced pro-inflammatory cell death. In addition, LtxA stimulated differentiation towards osteoclasts-like cells in LPS-treated THP-1 cells.